2020
DOI: 10.2147/ijn.s240359
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dual-Ligand Functionalized Core-Shell Chitosan-Based Nanocarrier for Hepatocellular Carcinoma-Targeted Drug Delivery</p>

Abstract: Introduction: Hepatocellular carcinoma represents a major health problem with the related death numbers still increasing. Active targeting is considered an attractive choice for the development of selective therapeutics with limited side effects and improved efficiency. In this study, we report the design, development and evaluation of a novel dual-ligand functionalized core-shell chitosan-based nanocarrier for the selective delivery of doxorubicin (DOX) for treatment of hepatocellular carcinoma (HCC). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Therefore, it is reasonable to expect that MNE does not raise blood glucose in HCC rats. In the present work, no significant changes were observed in urea and creatinine levels of HCC rats, which were also reported by some other researchers (Hefnawy, Khalil, Arafa, Emara, & El-Sherbiny, 2020;Kumar, Vijayalakshmi, & Saravanan, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is reasonable to expect that MNE does not raise blood glucose in HCC rats. In the present work, no significant changes were observed in urea and creatinine levels of HCC rats, which were also reported by some other researchers (Hefnawy, Khalil, Arafa, Emara, & El-Sherbiny, 2020;Kumar, Vijayalakshmi, & Saravanan, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Another way is the conjugation of GA with CS by a click reaction, by the activation of GA through the formation of the O-acylisourea ester and its stabilization with the addition of N-hydroxysuccinimide, and then favoring the formation of amine in the presence of CS [87]. The conjugation was confirmed by 1 H-NMR and FTIR analyses.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 93%
“…In addition to the determination of average particle size performed by dynamic light scattering (DLS) and transmittance electronic microscopy (TEM), other techniques have also been used in order to confirm the synthesis of ligands with different types of nanosystems. In studies with GL and GA, nuclear magnetic resonance (NMR) [80][81][82][83][84][85] and Fourier transform infrared spectroscopy (FTIR) [81,82,[86][87][88] were commonly used.…”
Section: Functionalized Nanoparticles With Glycyrrhizic Acid (Gl) or Glycyrrhetinic Acid (Ga)mentioning
confidence: 99%
“…Kai Jiang et al utilized the pH-sensitive nature of chitosan polymers to deliver a hydrophobic drug, namely ursolic acid, into endosomes (pH < 5.5) and reported the suppression of cancer cell growth [72]. The derivatization of chitosan polymers broadens opportunities such as dual-ligand functionalization [73], co-polymerization to develop amphoteric block co-polymers [11], co-delivery of drug molecules and oligonucleotides [68], and improving solubility [70]. Zhu et al reported that chitosan derivative N-succinyl-N -octyl chitosan self-assembles to form micelles due to its amphipathic nature, and conjugation with folic acid imparts a targeting nature to the micelles [74].…”
Section: Covalent Modificationsmentioning
confidence: 99%